Evaluating complex interventions in international development - and Masset, Edoardo; Shrestha, S.; Juden, M. (CEDIL, 2021)
This paper reviews promising methods for the evaluation of complex interventions that are new or have been used in a limited way. It offers a taxonomy of complex interventions in international development and draws on literature to discuss several methods that can be used to evaluate these interventions. Complex interventions are those that are characterised by multiple components, multiple stakeholders, or multiple target populations. They may also be interventions that incorporate multiple processes of behavioural change. While such interventions are very common and receive a large proportion of development aid budgets, they are rarely subject to rigorous evaluations. The CEDIL Methods Working Paper, ‘Evaluating Complex Interventions in International Development’, reviews promising methods for the evaluation of complex interventions that are new or have been used in a limited way. It offers a taxonomy of complex interventions in international development and draws on literature to discuss several methods that can be used to evaluate these interventions. The paper focuses its attention on methods that address causality and allow us to state conclusively whether an intervention works or not. It shows that several rigorous methods developed in different disciplines can be adapted and used to evaluate complex interventions in international development.